Cancer and occupational exposure to inorganic lead compounds: a meta-analysis of published data. Issue 2 (February 1995) - Fu, H; Boffetta, P
Abstract : OBJECTIVES–To review and summarise the epidemiological evidence on the carcinogenicity of occupational exposure to inorganic lead. METHODS–Case-control and cohort studies were reviewed and combined for meta-analysis. Fixed and random effect methods were used to estimate the summary effects. RESULTS–The combined results show a significant excess risk of overall cancer, stomach cancer, lung cancer, and bladder cancer, with relative risk ratios (RRs) and 95% confidence intervals (95% CIs) in the meta-analysis of 1.11 (1.05-1.17), 1.33 (1.18-1.49), 1.29 (1.10-1.50), and 1.41 (1.16-1.71) respectively. The RR (95% CI) for kidney cancer was also high, but did not reach significance (1.19 (0.96-1.48)). A separate analysis of studies of heavily exposed workers provided slightly increased RRs for cancers of the stomach (1.50) and lung (1.42). CONCLUSIONS–The findings from the workers with heavy exposure to lead provided some evidence to support the hypothesis of an association between stomach and lung cancer and exposure to lead. The main limitation of the present analysis is that the excess risks do not take account of potential confounders, because little information was available for other occupational exposures, smoking, and dietary habits. To some extent, the risk of lung cancer might be explained by confounders such as tobacco smoking and exposure to other occupational carcinogens. The excess risk of stomach cancer may also be explained, at least in part, by non-occupational factors. For bladder and kidney cancers, the excess risks are only suggestive of a true effect because of possible publication bias.